Analisis Kepuasan Pasien Rawat Jalan Terhadap Pelayanan Kesehatan Di RSUD Lubai Ulu Kabupaten Muara Enim Tahun 2023 - Purnawan, Tanto; Zaman, Chairil; Ekawati, Dianita (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
The hospital is one of the agencies authorized to provide health services to the wider community. The increasing number of existing hospitals encourages hospitals to be able to compete with other hospitals in providing the best possible service for consumer satisfaction. Patient satisfaction depends on the quality of health services. Patient satisfaction is one of the goals of improving the quality of health services. This research is a quantitative analytic observational method with a cross-sectional design which aims to analyze patient satisfaction with health services at Lubai Ulu Hospital, Muara Enim Regency in 2023. This research was conducted at Lubai Ulu Hospital, Muara Enim Regency in April-June 2023. Study population were all outpatients at Lubai Ulu Hospital, the sampling technique was accidental sampling with a sample size of 95 people. The results of this study indicate that the factors associated with patient satisfaction with health services are education p value = 0.023, responsiveness p value = 0.000, tangibles p value = 0.000 , reliability p value = 0.006 and empathy p value = 0,014. While gender p value = 0.513, assurance p value = 0.056 and knowledge p value = 0.411 there is no relationship with patient satisfaction with health services. The results of the logistic test showed that tangibles ( Exp B = 5.385) p Value 0.000 was the most dominant variable influencing patient satisfaction with health services. It was concluded that tangibles are very influential for patient satisfaction with health services at Lubai Ulu Hospital. For this reason, Lubai Ulu Hospital can improve the quality of health services which consist of providing medical infrastructure and equipment according to Class D hospital standards.